Afro communal territoriality in Esmeraldas: an imaginary at risk - Cárdenas, Esthefanía (El Outsider: Journal of International Relations and Political Science, 2022)
The Afro/Black communal territory of the cantons of San Lorenzo and Eloy Alfaro, in Esmeraldas, has been an example of the resistance of this population since colonial times. The largely racialized and impoverished communities that inhabit these spaces went through long processes of defense against various attempts at territorial dispossession that allowed them, up to a certain point, to preserve their autonomy and collective tradition. However, the territorial imaginaries promoted by the nation-state and the international actors that promote extractivist development, currently represent a threat to the perceptions of communal belonging of these Afro populations. For that reason, this article argues that the struggle for the defense of these Afro communal territorialities is in danger and as a result these populations have become fragmented and their collective well-being has been threatened.
Keywords: Afro/black communes; Esmeraldas; territory; extractivism; nation state; racialization; collective belonging